FAKTOR-FAKTOR MOTIVASI KERJA PEGAWAI KANTOR CAMAT SINGKUT KABUPATEN SAROLANGUN - Atikasari, Reni Indar (Jurnal Dinamika Manajemen, 2015)
This study only focuses on what factors influence employee motivation in the Singkut District Office, Sarolangun Regency. The research method used is descriptive research using a questionnaire as a tool to collect data. The population in this study were employees of the Singkut District Office, Sarolangun Regency. The data collection procedure was carried out by distributing questionnaires with a sample of all employees of the Singkut District Office, Sarolangun Regency, totaling 34 employees. The results of this study indicate that the work motivation of the employees of the Singkut District Office, Sarolangun Regency, is not good, or less motivated. Of the five motivational factors used, namely physiological needs, safety needs, social needs, esteem needs, and self-actualization needs. It is known that for each factor the average value is: Physiological Needs Factor with an average of 126 meaning work motivation, Safety Needs Factor with an average of 108.33 meaning less work motivation, Social Needs Factor with an average of 97 .66 means the work is less motivated, the Self-Esteem Needs Factor with an average of 115.66 means the work is less motivated, and the Self-Actualization Needs Factor with an average of 127.66 means the work is motivated. If seen as a whole, the average work motivation of the Singkut District Office, Sarolangun Regency is 115, which means that the work motivation is lacking.